De mãos dadas em território camponês tecendo uma proposta educativa e formativa para o trabalho - Fonseca, Marlece Melo (2020)
The research entitled "Hand in hand in peasant territory weaving a formative proposal for work" presents itself as a contribution to the discussions on education through work and the collective and participative construction of the educational proposal of a non-governmental organization in peasant territory. The question that guided this research was: “how to build an educational and training proposal based on work as an educational principle for non-formal space in peasant territory?”. The study aimed to contribute to the construction of an educational and training proposal through participatory planning in non-formal space in peasant territory guided by work as an educational principle and incorporated participatory planning (GANDIN, 1994, 2002) as a theoretical framework to support the structure of the educational proposal. This research appropriates the qualitative approach using action research in the perspective of Barbier (2007) and was carried out at the Centro Educativo De Mãos Dadas located in the rural area of the municipality of Parintins-AM. Three rounds of conversations were held that focused on the Center and its articulation with the community and three workshops based on the stages of participatory planning, discussing the situational framework, diagnosis, and programming. The data were analyzed by means of the categorical analysis which, according to Bardin (2011), consists of breaking up the text into categorized and grouped categories according to inferential approximations. As a result, it became evident that the Centro De Mãos Dadas develops educational and training work and indicates the need for participatory planning to carry out pedagogical activities in rural areas. The Educational Product proposes a set of workshops that will subsidize the construction of an educational and training proposal for education through work in peasant territory based on participatory planning and work as an educational principle.